INOVASI PENGHITUNGAN KENDARAAN PADA MANAJEMEN PARKIR DENGAN SENSOR INFRARED BERBASIS IOT - Hanifatus Sa’diyah Widihasaniputri; Wahju Tjahjo Saputro; Hamid Muhammad Jumasa (TEKNIMEDIA: Teknologi Informasi dan Multimedia, 2025)
Traffic and parking management are still major issues in urban areas. The average driver spends 7.8 minutes to find a parking space, and 30% of traffic congestion is caused by finding a parking space.This research focuses on designing a system that adopts infrared sensors and IoT to detect the number of vehicles in a smart parking system.The method used is the prototype method. The process starts with activating the device to monitor vehicles entering and leaving the parking area. Next, the detected vehicles will be checked, if the vehicle enters then the system automatically reduces the number of available parking slots. Conversely, if the vehicle exits, the system adds one slot to the number of available parking slots. the results of component testing carried out, found that all components, including infrared sensors, PIR sensors, LCDs, servo motors, and Arduino Uno R3 microcontrollers, have functioned properly. This is supported by the average system response delay test which only reaches 1.50 seconds and is included in the responsive category for smart parking systems